Identification Of Central Lombok Community Knowledge About the Importance of Covid-19 Vaccines - Dewi Nur Sukma Purqoti; Harlina Putri Rusiana; Ernawati Ernawati; Baiq Rulli Fatmawati (Jurusan Keperawatan, Poltekkes Kemenkes Mataram, 2022)
Efforts in the framework of prevention and control of Covid-19 is to form herd immunity in the community that can be done by successful vaccination programs. Vaccination is an important key in suppressing the spread of the Covid-19 virus, in addition to the behavior of maintaining physical distance, washing hands, and using masks must be completely applied and obeyed by all levels of society, although not a few people who ignore and are not disciplined in implementing the Health protocol on the grounds that they have received vaccinations. This is influenced by public knowledge related to the Covid-19 vaccine. The purpose of this study was to determine the level of public knowledge related to the Covid-19 vaccine.This study used descriptive methods with a crosssectional approach. This study was conducted in the central Lombok Janapria village in April-May 2021 with a sample of 81 respondents. The instrument used is a questionnaire. The data analysis used is univariate analysis. The results of the study found that respondents aged 20-30 years as many as 54 people (66.7%), the most gender is women 55 people (67.9%), The majority of respondents were students as many as 30 people (37%), and the level of knowledge about the Covid-19 vaccine in the janapria village community was mostly in the good category of 47 respondents (58%). The conclusion of the janapria village community of Lombok is in the category of good knowledge about the importance of the Covid-19 vaccine.